Reception Analysis Masyarakat Surabaya terhadap Wacana Presiden 3 Periode - Rizal Wahyu Saputra; Dyva Claretta Claretta (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This research is motivated by the 3-period presidential discourse in the Indonesia Lawyers Club (ILC) program. This study aims to determine public acceptance of the 3-term presidential discourse on the YouTube channel Indonesia Lawyers Club (ILC) episode